Service management and marketing principles: Competing in the service economy - Kandampully, Jay; Solnet, David J. (London Routledge, 2024)
This book explores the service economy and challenges that all organizations face as goods and services make way for a world where customers (B2C) and businesses (B2B) seek seamless, thoughtful, and exceptional experiences. This book introduces readers to a range of interrelated topics and the application of service management and marketing theories which are fundamentally critical to the success of all enterprises seeking competitive advantage through enhanced customer experience.
Keywords: BUSINESS & ECONOMICS / Industries / Service Industries; Industries, Service Industries; Marketing